Labor Share Decline and Intellectual Property Products Capital - Koh, Dongya; Santaeulàlia-Llopis, Raül; Zheng, Yu (Econometrica, 2020)
We study the behavior of the U.S. labor share over the past 90 years. We find that the observed decline of the labor share is entirely explained by the capitalization of intellectual property products in the national income and product accounts.